Cultural boundary conditions in SSCM: Bridging western theory and local practice - Makprang, Kittinun; Mokkhamakkul, Tartat; Tangmanee, Chatpong (International Journal of Management and Sustainability, 2025)
This study investigates how sustainable supply chain management (SSCM) theories developed in Western contexts perform in hierarchical and relationship-oriented cultures, with Thailand as the empirical setting. The purpose is to identify cultural boundary conditions that influence whether market orientation, dynamic capabilities, and managerial commitment lead to sustainable practices and performance outcomes. A quantitative explanatory design was applied, combining survey data from 159 publicly listed firms across eight industries with secondary sustainability performance disclosures. Partial least squares structural equation modeling (PLS-SEM) and confirmatory composite analysis (CCA) were used to ensure measurement validity and test hypotheses. Three key findings emerge. First, market orientation and dynamic capabilities significantly predict managerial commitment, explaining 80.3 percent of its variance and showing cross-cultural robustness at the managerial cognition level. Second, a cultural implementation paradox is identified, as managerial commitment does not translate into sustainable practice adoption, reflecting authority–consensus disconnections common in hierarchical contexts. Third, sustainable practices negatively affect social performance while showing no significant impact on economic or environmental outcomes, indicating social disruption effects that challenge the universality of the triple bottom line framework. The practical implication is that multinational firms and policymakers in emerging markets should adapt Western SSCM models to local contexts, preserving social capital and aligning with consensus-based decision-making.